2022
DOI: 10.1002/iub.2625
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid ameliorates acetaminophen‐induced acute liver injury by promoting AMPK‐mediated protective autophagy

Abstract: Acetaminophen (APAP), one of the most widely used antipyretics and analgesics, principally results in acute liver injury (ALI) in developed countries when taken overdose. Ferulic acid (FA) is a natural polyphenol compound existing in many plants that has free radical scavenging, anti-inflammatory, and liverprotective properties. However, the effect and underlying mechanism of FA in treating APAP-induced ALI have not been fully elucidated. Herein, we established a mouse model of APAP-induced ALI and used APAP-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…However, caloric restriction resulted in an AMPK-regulated increase in catabolic processes, such as the turnover of mitochondria. AMPK activation and mitophagy are well-established to reduce the severity of APAP-induced mitochondrial damage due to lower ROS levels [58][59][60][61][62]. Paradoxically, starvation may therefore have a similar effect than glucose administration, i.e., it reduces the impact of mitochondria-dependent cellular energy production and ROS formation during APAP intoxication.…”
Section: Discussionmentioning
confidence: 99%
“…However, caloric restriction resulted in an AMPK-regulated increase in catabolic processes, such as the turnover of mitochondria. AMPK activation and mitophagy are well-established to reduce the severity of APAP-induced mitochondrial damage due to lower ROS levels [58][59][60][61][62]. Paradoxically, starvation may therefore have a similar effect than glucose administration, i.e., it reduces the impact of mitochondria-dependent cellular energy production and ROS formation during APAP intoxication.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, an APAP-induced acute liver injury (ALI) mouse model was established. It was found that APAP treatment could lead to liver necrosis ( Wu et al, 2022 ). APAP can cause a significant increase in serum ALT, AST and oxidative stress.…”
Section: Protective Effect On Liver Injurymentioning
confidence: 99%
“…FA further inhibited APAP-induced hepatocyte apoptosis by increasing Bcl-2 and decreasing caspase-3 and Bax protein levels. The results of functional enrichment suggest that FA is involved in the regulation of the mitogen-activated protein kinase (MAPK) signalling pathway and other metabolic processes ( Wu et al, 2022 ).…”
Section: Protective Effect On Liver Injurymentioning
confidence: 99%
“…Furthermore, ferulic acid (FA) isolated from multiple herbs was also reported to ameliorate APAP-induced ALI by promoting the AMPK-mediated protective autophagy. The addition of AMPK inhibitor compound c abolished FA-induced up-regulation of autophagy activation-associated proteins such as LC3, ATG5 and eventually the hepatoprotective activity of FA [ 137 ]. From a different perspective, a researcher found that APAP could induce harmful overactivation of autophagy, which could be rectified by alpha-mangostin (α-MG) derived from Garcinia mangostana by activating the AKT-mTOR pathway.…”
Section: Potential Therapeutic Effects Of Natural Products On Liver D...mentioning
confidence: 99%